Efektifitas Bahan Ajar Buku Panduan PembelajaranKebencanaan Kabupaten Klaten Pada Bencana Gempa BumiMelalui Strategi Card Sort Terhadap Hasil Belajar SiswaEkstrakurikuler Sekolah Siaga BencanaDi SMK Kristen 5 Klaten - Rahmadi, Ibnu Wahid, Drs. Dahroni M.Si (2016)
Christian vocational school 5 located in Tegalyoso the village of Southern Klaten District of Klaten, Central Java province. Regional Disaster Management Agency (BPBD) Klaten have instructional materials guide books disaster in which there are materials on disaster. The strategies used influence on student learning outcomes. This study uses a sort card strategy aims to test the effectiveness of the instructional materials, as an active strategy can affect students in receiving knowledge appropriate to the learning objectives. This type of research is quantitative experimental method. The population in this study amounted to 62 students by using samples of two classes, extracurricular school disaster preparedness as an experimental class and extracurricular type the ten fingers as the control class. Grading seen from the average value of students in a repeat of mid semester of the academic year 2015/2016. Learning in the classroom lecture control using conventional methods while the experimental class using the strategy card sort. Grade control in this study is an extracurricular type the ten fingers totaling 27 students, where as the experimental class is an extracurricular school disaster preparedness totaling 35 students. Mechanical testing instruments used validity, reliability test. Data taken form the value pretest and posttest then processed with data analysis techniques using the technique of homogeneity, normality test, and test hypotheses. Testing data using SPSS 21. The results of the processing of the data showed the average value of 65.92 posttest experimental class while conveniently indicates an average value of 77.14 posttest. Through hypothesis testing the control class and experimental class using the Independent Sample T Test showed the Sig (2-tailed) is lower than the probability value of 0.05 then H0 is rejected. The conclusion that there was an increase in student learning outcomes significantly by using teaching materials guide books disaster Klaten regency in the earthquake through a strategy card sort in vocational Christian 5 Klaten